Strategy For The Development of Kepok Banana Farming (Musa Sp) In The Outermost Islands of Enggano - Rizki Amelia Rosyada; Basuki Sigit Priyono; Indra Cahyadinata (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2023)
Enggano has an agricultural area of 8.618 hectares with production in 2019 of 10.040 tonnes. This research aims (1) to identify internal and external factors in the development of bananas; (2) to analyze alternative formulations for appropriate strategies; and (3) to set strategic priorities in the developing of banana. The research began with the collection of data interviews and the distribution of angket. The data was then processed using SWOT analysis by creating the IFAS and EFAS matrix, as well as to determine the appropriate strategy using QSPM analysis. The number of respondents was 28 people (25 banana farmers, 1 food and holticultural crops, 1 land science lecturer and 1 agroecology lecturer). The results of the research are based on the IFE analysis, an internal factor that affects the development strategy of bananas on the island of Enggano from the main strength is that bananas are the best products in the island. While the main weakness is the lack of cooperation with existing partners. Based on the EFE analysis, the external factor that influences the strategy of development of banana in the islands of Enggano of the main opportunity is the high demand of the market. The appropriate strategy to use the results of the SWOT and QSPM analysis is to increase production through the expansion of land with suitable climate/weather conditions and the availability of production input and experience to meet the high demand of the market.